Variations in Aging, Gender, Menopause, and Obesity and Their Effects on Hypertension in Taiwan - Shu C. Chen; Tsai C. Lo; Jui H. Chang; Hsien W. Kuo (International Journal of Hypertension)
Aim. We assessed obesity, sex, menopause, and gender differences on hypertension in a Hakka-majority Taiwanese sample. Methods. 9621 subjects aged 20 and over participated in this community-based study. Trained nurses collected blood pressure (BP) measurements and anthropometric indices, including weight, height, hip circumference (HC), waist circumference (WC), body mass index (BMI), waist to height ratio (WHtR), and waist to hip ratio (WHR). Results. Levels of systolic and diastolic BP significantly increased at a dose-dependent relationship based on four anthropometric indices (BMI, WC, WHR, and WHtR); the slopes for SBP and DBP differed. After controlling for other covariates using multivariate logistic regression, we found the adjusted odds ratios (OR) of hypertension to be significantly related to the four anthropometric indices. Notably, the effect of obesity on the ORs for hypertension was considerably higher in premenopausal women, but we found no such phenomenon among men. BMI, WC, WHR, and WHtR had significant linear associations with BP. Conclusion. Obesity indices are significantly correlated with the risk of hypertension across gender and age, with BMI having the highest relative potency. The effect of obesity on the risk of hypertension is especially high in premenopausal women, implying a relationship between hormones and hypertension.